Systemic Weber-Christian disease - Milner, R. D. G. (1965)
A patient suffering from Weber-Christian panniculitis was found at necropsy to have similar lesions in the visceral adipose tissue. When the lesions occur internally, diagnosis during life is complicated by the difficulty of examining visceral adipose tissue and the disease may often go unrecognized, but patients suffering from Weber-Christian panniculitis should be investigated bearing in mind the possibility of internal lesions. Only 11 cases confirmed by necropsy appear to have been reported hitherto. The aetiology remains obscure. It is suggested that the name `systemic Weber-Christian disease' be applied when the lesions occur in adipose tissue other than the panniculus adiposus and that the term `Weber-Christian panniculitis' be used when the lesions are confined to the subcutaneous adipose tissue.